Cyber–physical testbed for Wide Area Measurement System employing IEC 61850 and IEEE C37.118 based communication - Astha Chawla; Mohd. Asim Aftab; S.M. Suhail Hussain; B.K. Panigrahi; Taha Selim Ustun (Energy Reports, 2022)
Wide Area Measurement Systems (WAMS) are well known for enhancing situational awareness of the grid using IEEE C37.118 phasors from Phasor Measurement Units (PMUs). Recently introduced IEC 61850-90-5 Routable Sample Values (R-SV) have proven promising to communicate timestamped synchrophasors to the control center, fulfilling the purpose. In wide area protection and control schemes, the communication of synchrophasors to the control center is also followed by sending back a supervisory decision signal (based on synchrophasor data) to the physical devices in the field. Development of WAMS testbeds for implementation and assessment of such schemes have often been addressed only from IEEE C37.118 PMU phasors’ perspective alone. This paper presents a comprehensive cyber–physical WAMS testbed capable of real-time communication of synchrophasors using both IEEE C37.118 PMU phasors and IEC 61850-90-5 R-SV. It also facilitates status and feedback signal communication between the control center and substations using IEC 61850-90-5 Routable GOOSE (R-GOOSE). The developed testbed integrates a real-time digital simulator (RTDS), industry-standard hardware devices such as PMUs, Phasor Data Concentrator (PDC), IEDs, Global Positioning System (GPS) synchronization clock, network components, and software components such as IEC 61850 emulator tools. It can be used for end-to-end implementation of a myriad of wide area monitoring protection and control (WAMPAC) applications. It can further facilitate vulnerability analysis of WAMS components, analyze the impact of cyber-attacks on critical applications, and then test and validate various security solutions for cyber resiliency of WAMPAC applications.